‘HoneySweet’ (C5), the First Genetically Engineered Plum pox virus–resistant Plum (Prunus domestica L.) Cultivar - Scorza, Ralph; Ravelonandro, Michel; Callahan, Ann; Zagrai, Ioan; Polak, Jaroslav; Malinowski, Tadeusz; Cambra, Mariano; Levy, Laurene; Damsteegt, Vern; Krska, Boris; Cordts, John; Gonsalves, Dennis; et al. (ASHS, 2020)
Origin ‘HoneySweet’ originated as a seedling from the open pollination of ‘Bluebyrd’ plum (Scorza and Fogle, 1999). The pollen parent of ‘HoneySweet’ is unknown. ‘HoneySweet’ was originally selected in vitro as a regenerated shoot from a hypocotyl slice that had been transfected with Agrobacterium tumefaciens EHA 101 carrying the plasmid pGA482GG/PPV-CP-33 (Scorza et al., 1994). The regenerated, transgenic shoot, coded as C5, along with other transgenic shoots, was rooted in vitro and transferred to a greenhouse. Following greenhouse testing using graft and aphid inoculations with the M and D strains of Plum pox virus (PPV), C5 (later patented as ‘HoneySweet’), was asexually propagated by bud grafting on to standard rootstocks, including Prunus persica (GF305 peach seedlings), Prunus domestica (European plum seedlings), Prunus myrobalan, and GF 8-1 (Prunus cerasifera × P. munsoniana). An overview of the development of ‘HoneySweet’ plum and molecular characterization can be found in Scorza et al. (2013a).